PENGARUH PEMBERIAN PUPUK ORGANIK CAIR KULIT PISANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SAWI (Brassica juncea) - Siswa Panjang Hernosa (JURNAL AGROPLASMA, 2019)
The design is the design of a randomized (RAK) factorial one factor that is five treatments: P0: 0 ml / polybag, P1: 125 ml / polybag, P2: 250 ml / polybag, P3: 375 ml / polybag, P4: 500 ml / polybag, and continued with Duncan test. Parameters measured were plant height (cm), leaf area (cm), plant fresh weight (g). From Reviews These results we concluded as follows: (1) Providing a liquid organic fertilizer waste vegetable markets significantly affected plant height swamp land at the age of 14 HST and 28 HST, (2) Organic fertilizer liquid waste vegetable market Significantly Affect the broad leaf kale land at 14 HST and 28 HST. (3) Provision of vegetable waste liquid organic fertilizer market real impact on plant fresh weight. Keywords: oganik liquid manure, banana weevil, growth, land water spinach